First Report of Globisporangium (Pythium) mastophorum causing Damping-off / Root Rot on Parsley in Slovenia - Zajc, Janja; Kovačec, Eva; Prislan, Ursa; Podboj Ronta, Aleksandra; Žerjav, Metka; Schroers, Hans-Josef (Plant disease, 2024)
Pythium-like species cause damping-off symptoms of various hosts, including umbelliferous crops. In April 2023, parsley plantlets ( ), showing stunted growth, yellowing, decayed roots and damping-off, were obtained from a nursery in central Slovenia, where parsley was grown in polystyrene trays in a greenhouse. Nearly 30% of plants were symptomatic. Sampled roots of ten plants contained ornamented oogonia (avg. 33.3 ± 1.4 µm in diam) with conical projections (5.2 ± 0.5 µm long) (Figure S1 A, B) in microscopically analyzed squash mounts. The pathogen was isolated from root pieces treated for surface disinfection with 0.5% sodium hypochlorite for 30 s, and washed with sterile water. Four 1-2 mm root pieces were taken from each of 10 plants, plated on the selective medium P5ARP, and incubated at 21 °C. Mycelia emerging from root pieces were transferred to carrot piece agar (CPA). Twenty-two equally looking oomycetous colonies were obtained; all sampled plants were infested. Oogonia formed by all colonies were similar to those observed on decayed roots and suggested that is the causal disease agent. Analyses of partial β-tubulin (Kroon et al. 2004) and mitochondrial cytochrome c oxidase I (COI) gene sequences (Robideau et al. 2011) confirmed the identification. Obtained COI (Genbank accession number OR725417) sequence was 100% identical to that from strain CBS 375.72 (EU350523), whereas the β-tubulin sequence (OR725416) corresponded to 99.6 % pairwise identity (KJ595502). Further, pathogenicity of an obtained isolate was tested on 4 wk-old curly leaf (cv. Petra F1) parsley. Half of a 7 d-old CPA culture, consisting of mycelium and oogonia, was finely cut and mixed with ca 50 ml of nonsterile commercial substrate (Potgrond H, AGRO-FertiCrop) in each of six 400 ml pots. Pots were filled with ca 300 ml additional substrate, into which 5 parsley seedlings were planted. Control plants were treated equally but with sterile CPA. Plantlets were watered with sterile tap water and held at ambient light conditions and temperature (night 18 °C - day 23 °C). After 14 d, inoculated plants started wilting and yellowing and showed stunted growth. After 21 d, roots were severely decayed and the seedlings damped-off (Figure S1 C). Four pieces each from 10 decayed roots were plated. Thirty-one pieces revealed pythium-like colonies. Obtained isolates were morphologically identical to the strain used for inoculation and identified as . Control plants developed no foliar or root symptoms and no pythium-like species was obtained. Agricultural advisors observed occurrence of parsley damping-off also in other nurseries in Slovenia what may lead to spreading the pathogen to parsley in production fields and private gardens. The case emphasizes the need for implementing phytosanitary measures in order to eliminate primary inoculum. Reports from field-infected plants showed that is a pathogen of parsley in Australia (Petkowski et al. 2013) and the USA (Tsuchida et al. 2018), and celery in the Czech Republic (Šafránková and Holková 2017). Others isolated from parsley in The Netherlands (online database of the Westerdijk Fungal Biodiversity Institute, strain CBS 243.86). However, the here described case is, to the best of our knowledge, one of the rare documentations of damping-off due to in Europe (Šafránková and Holková 2017) and the first in Slovenia. Funding: The work was funded by the Ministry of Agriculture, Forestry and Food of Slovenia, and Slovenian Research and Innovation Agency (ARIS Programs P4-0431 and P4-0072).